ENRICH EDUCATIONAL CONTENT THROUGH MULTIMEDIA RESOURCES USING DIGITAL TECHNOLOGIES (Conference Zone, 2022)
In this article, we will talk about the use of digital technologies, the wide use of information and communication technologies in education, increasing the effectiveness of education through multimedia resources, automated education systems.